Building capacity through action research: reflections on working with low-carbon communities in the UK. Issue 6 (3rd June 2017) - Lucas, Karen; Hamilton, Jo; Mayne, Ruth
ABSTRACT: This paper describes a four-year programme of "action research" (AR) undertaken with six communities in the UK, referred to as the Evaluating Low-Carbon Communities (EVALOC) project. The research combined a programme of research events with phased household-level monitoring of energy and carbon-reduction interventions. The carbon-reduction interventions were funded by the UK's Department of Energy and Climate Change prior to the onset of the research. AR has recently been adopted within the context of environmental behaviour change programmes in the UK, with a number of methodological challenges. The EVALOC project's challenges included developing a collaborative research design; building reciprocity between the researchers and research participants; dealing with biases and burdens in the research process; ensuring analytical rigour in the interpretation of the primarily qualitative evidence and dealing with the long-term and process-driven outcomes that arise from such interactions. This paper explores and discusses the challenges of AR in relation to selected research outcomes from EVALOC. We conclude by suggesting that the AR approach has helped to build capacity in the participating low-carbon communities (LCCs), through supporting the design, delivery and evaluation of their energy and carbon-reduction activities.